1989
DOI: 10.1159/000216082
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Factor XIII Deficiency with Multiple Benign Breast Tumours and Successful Pregnancy with Substitutive Therapy

Abstract: A 34-year-old woman with congenital factor XIII (FXIII) deficiency and multiple connective tissue tumours is reported. The subunit a of FXIII was totally absent in her plasma, platelets and histiocytes of breast fibroadenomas and considerably reduced in the monocytes (below 5%). The plasmatic level of subunit b was also reduced (25%). She had a bleeding tendency and habitual abortions. Fresh frozen plasma therapy permitted a successful pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 13 publications
(21 reference statements)
0
24
0
Order By: Relevance
“…This concept is also supported by the fact that substitution therapy with FXIII concentrates permitted normal pregnancies in human patients with FXIII deficiency. [18][19][20] Homozygous fibrinogen-deficient mice also displayed miscarriage 21,22 because of intrauterine bleeding around 10 dG. Again, it is suggested that maternal fibrinogen plays an essential role in the maintenance of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…This concept is also supported by the fact that substitution therapy with FXIII concentrates permitted normal pregnancies in human patients with FXIII deficiency. [18][19][20] Homozygous fibrinogen-deficient mice also displayed miscarriage 21,22 because of intrauterine bleeding around 10 dG. Again, it is suggested that maternal fibrinogen plays an essential role in the maintenance of pregnancy.…”
Section: Resultsmentioning
confidence: 99%
“…For each pregnancy, the following data were collected: bleeding during pregnancy and gestational age at the time of bleeding, miscarriage and gestational age at time of miscarriage, prophylactic treatment prior to and/or during pregnancy; mode of delivery; gestational age at delivery, presence of antenatal complications; occurrence of postpartum haemorrhage; other postpartum complications; and neonatal outcome. [10,46] included 13 women who were also reported individually as case reports [11,12,16,17,22,24,28,30,[32][33][34][35]. These 13 cases were included only once, making the total number of women in the review 121 women.…”
Section: Data Extractionmentioning
confidence: 99%
“…Menorrhagia (heavy menstrual bleeding, HMB) was reported in 31 (26%) women, making it the second most common bleeding symptom [10][11][12]21,25,28,30,32,33,35,37,38,41,42,44,45]. Umbilical bleeding was the most common bleeding symptom and reported in 33 (27%) women.…”
Section: Gynaecological and Other Bleeding Symptomsmentioning
confidence: 99%
See 2 more Smart Citations